An investigation of WNT pathway activation and association with survival in central nervous system primitive neuroectodermal tumours (CNS PNET) - Rogers, H A (Nature Publishing Group, 2009)
Central nervous system primitive neuroectodermal tumours (CNS PNET) are high-grade, predominantly paediatric, brain tumours. Previously they have been grouped with medulloblastomas owing to their histological similarities. The WNT/β-catenin pathway has been implicated in many tumour types, including medulloblastoma. On pathway activation β-catenin (CTNNB1) translocates to the nucleus, where it induces transcription of target genes. It is commonly upregulated in tumours by mutations in the key pathway components APC and CTNNB1. WNT/β-catenin pathway status was investigated by immunohistochemical analysis of CTNNB1 and the pathway target cyclin D1 (CCND1) in 49 CNS PNETs and 46 medulloblastomas. The mutational status of APC and CTNNB1 (β-catenin) was investigated in 33 CNS PNETs and 22 medulloblastomas. CTNNB1 nuclear localisation was seen in 36% of CNS PNETs and 27% of medulloblastomas. A significant correlation was found between CTNNB1 nuclear localisation and CCND1 levels. Mutations in CTNNB1 were identified in 4% of CNS PNETs and 20% of medulloblastomas. No mutations were identified in APC. A potential link between the level of nuclear staining and a better prognosis was identified in the CNS PNETs, suggesting that the extent of pathway activation is linked to outcome. The results suggest that the WNT/β-catenin pathway plays an important role in the pathogenesis of CNS PNETs. However, activation is not caused by mutations in CTNNB1 or APC in the majority of CNS PNET cases.